Hubungan Perilaku Bullying dengan Kemampuan Interaksi Sosial pada Remaja - Rahayuningrum, Dwi Christina; Apriyeni, Emira; Patricia, Helena (Universitas Malahayati, 2024)
ABSTRACT Bullying cases at school top the list of public complaints to the child protection commission (KPAI) in the education sector. West Sumatra has a prevalence rate of 28% of children experiencing violence at school, while 29% of children who experience violence at school are 29%. The aim of this research is to determine the relationship between bullying behavior and social interaction skills among teenagers at SMPN 26 Padang. Cross sectional study research design. The research was carried out in September 2023, with a population of 588 people and a sample of 240 students in grades 7 and 8 of SMP N 26 Padang. Sampling was taken using a proportional random sampling technique using a research instrument in the form of a questionnaire. The research results showed that more than half of the respondents (52.1%) had less interaction, more than half of the respondents (59.6%) had high levels of bullying behavior. The results of the Chi-Square test showed that the relationship between bullying behavior and social interaction was obtained with a value of p=0.000. It was concluded that social interaction is one of the factors causing bullying behavior in students. It is recommended that the school improve extracurricular activities at school Keywords: Bullying Behavior, Social Interaction, Teenagers ABSTRAK Kasus bullying disekolah menduduki peringkat teratas pengaduan masyarakat ke komisi perlindungan anak (KPAI) di sektor pendidikan. Sumtera Barat memiliki angka prevalensi anak mengalami kekerasan di sekolah sebesar 28%, sedangkan anak pelaku kekerasan disekolah 29%.. Tujuan penelitian ini untuk mengetahui hubungan perilaku bullying dengan kemampuan interaksi sosial pada remaja di SMPN 26 Padang. Desain penelitian cross sectional study. Penelitian dilaksanakan pada bulan September 2023, dengan jumlah populasi 588 orang dan sampel 240 orang siswa kelas 7 dan 8 SMP N 26 Padang. Pengambilan sampel dengan teknik proportional random sampling dengan menggunakan instrument penelitian berupa kuesioner. Hasil penelitian didapatkan lebih dari separuh responden (52,1%) dengan interaksi yang kurang, lebih dari separuh responden (59,6%) dengan perilaku bullying yang tinggi. Hasil uji Chi-Square didapatkan hubungan antara perilaku bullying dengan interaksi sosial diperoleh nilai p=0,000. Disimpulkan bahwa interaksi sosial merupakan salah satu faktor terjadinya perilaku bullying pada siswa. Disarankan kepada pihak sekolah untuk meningkatkan ekstrakulikuler disekolah Kata Kunci: Perilaku Bullying, Interaksi Sosial, Remaja